Diverticular perforation of terminal ileum associated with chemotherapy for non-small cell lung carcinoma: a case report. Issue 4 (12th April 2023) - Kasuga, So; Abe, Shinya; Nozawa, Hiroaki; Sasaki, Kazuhito; Murono, Koji; Emoto, Shigenobu; Matsuzaki, Hiroyuki; Yokoyama, Yuichiro; Nagai, Yuzo; Yoshioka, Yuichiro; Shinagawa, Takahide; Sonoda, Hirofumi; et al.
Abstract: A 71-year-old man was diagnosed with advanced non-small cell lung carcinoma and treated with chemotherapy developed ileocecal diverticulitis three times over the last 2 months of receiving second-line treatment. During the fourth diverticulitis event, the patient presented with fever and abdominal pain, worsening after 5 days. Abdominal computed tomography showed ascites and intra-abdominal free air, suggesting bowel perforation with acute diffuse peritonitis. We performed emergency surgery; the surgical findings showed diverticulosis with perforated diverticula in the ileocecal region. We performed ileocecal resection, an ileostomy and a mucous fistula of the ascending colon. Histopathological examinations revealed pseudodiverticula at the perforation, where the mucosa was depressed through the muscularis propria. Hence, we diagnosed perforated ileal diverticulitis. Repeated diverticulitis triggered by chemotherapy might have resulted in perforation. Small bowel diverticula are rare, but diverticulitis can occur in patients receiving chemotherapy and with cases of unexplained fever and abdominal pain.